Implementasi Penanaman Nilai Pancasila pada Peserta Didik - Abdul Latief; Ade Rahayu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This study aims to see how to instill the value of Pancasila in students.The appropriate type of research is descriptive qualitative research.The research instrument used deep interview, observation and documentation.Research Subjects are Educators /Teachers.The focus of this research is the cultivation of the three principles of Pancasila by educators/teachers at SMA Negeri 1 Polewali, West Sulawesi Province.It was found that the implementation of the implanting of the three values of Pancasila in students was carried out by institutions/schools through the role of educators in the learning process in the classroom, through planting material, extracurricular activities, collaborative activities with local government partners, as well as community and parent participation.